-10=-9q+7

Simple and best practice solution for -10=-9q+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10=-9q+7 equation:


Simplifying
-10 = -9q + 7

Reorder the terms:
-10 = 7 + -9q

Solving
-10 = 7 + -9q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '9q' to each side of the equation.
-10 + 9q = 7 + -9q + 9q

Combine like terms: -9q + 9q = 0
-10 + 9q = 7 + 0
-10 + 9q = 7

Add '10' to each side of the equation.
-10 + 10 + 9q = 7 + 10

Combine like terms: -10 + 10 = 0
0 + 9q = 7 + 10
9q = 7 + 10

Combine like terms: 7 + 10 = 17
9q = 17

Divide each side by '9'.
q = 1.888888889

Simplifying
q = 1.888888889

See similar equations:

| 10+5f=9f-10 | | 6z-1=3+4z+6 | | (9n+4)+(9n+4)=180 | | 7n+2=-2+8n | | -u=-2u-7 | | 180(n-2)=5400 | | 5w-3=4w | | -9k+5=-10k-4 | | -9k+5=-10j-4 | | -2s-6=-s | | -34=8x-5(1-7x) | | 4j=5j-7 | | 4x+8=12x-12 | | 3g=-7+4g | | 9(t-5)+6t=5(3t+4)-10 | | m=-0.4n+28 | | y+y-y-y+y-1=18 | | -93-4v=-10v+3 | | 2x^4-9x^2-16x=0 | | 3h+3h-6h+2j-2=12 | | 2x^4-9x^2-16=0 | | 18j+2j-10j-5j-4j=16 | | 18j+2j-10-5j-4j=16 | | 13p-6p-5p=18 | | 9t+(3f)t+13= | | 27-×/4=x/5 | | 4+7x-3=9x+13-6x | | 6j+-2j+14j-7j+-9n-(-19)=-15 | | m(a+5)=Kfora | | -0.1x^2-x+31=0.1x^2+2x+11 | | 6j+-2j+14j-7j+-9-(-19)=-15 | | 0.2x^2+x-20=0 |

Equations solver categories